Model Seleksi Terbuka Perangkat Desa Berdasarkan Peraturan Bupati Kabupaten Demak No. 11 Tahun 2022 - Habibullah, Akhmad (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2024)
Since the enactment of the Village Law No. 6 of 2014, villages have become attractive again to be considered from all aspects, including their governance. One of the important things is the village apparatus. Since having financial autonomy for village funds, the public’s interest in becoming village officials has become increasingly high. Therefore, the selection process of village apparatus is an interesting thing to do and accompanied, so from the Government Science study program FISIP UPS Tegal in collaboration with Trimulyo Village, Guntur District, Demak Regency in collaboration with the community service process with village apparatus selection activities, the main purpose of this activity is to capture village apparatus that have quality according to the expectations of the desad committee and in accordance with the implementation instructions based on existing regulations. The implementation of this community service is carried out with the needs of existing activities, as for the several stages carried out in this service process the first. One of the stages carried out is observation, and the implementation of village apparatus selection activities. The results of the implementation of community service carried out are carried out in accordance with the provisions of existing regulations, first a computer-based Basic Proficiency Test, second a practical exam and finally an interview. The results of the service showed results in accordance with the existing stages, and the entire series of selection processes for existing village apparatus ran smoothly.